The politics of colonised subjectivity: A critical review of HA Bulhan's "Franz Fanon and the psychology of oppression" (1985) - Couve, Cyril (PINS-Psychology in Society, 2025)
The published studies of the work of Franz Fanon in the last twenty years reveal a glaring paradox. Despite the fact that Fanon was a trained psychiatrist and practicing psychotherapist, hence deeply influenced by a range of psychological theories amongst other, critical studies remain dominated by historians, political theorists and biographers. The Fanonian legacy has occasioned a mere trickle of serious appraisals by psychologists themselves despite its wide ranging appeal amongst black intellectuals and its considerable influence on American and South African Black Consciousness movements. H. Bulhan's book is thus a particularly welcome contribution to Fanonian scholarship as it constitutes the first major attempt by a trained psychologist to systematise Fanon's psychological writings. It is clear that Bulhan sees himself both as the guardian and continuator of Fanon's work, truncated as it was by his untimely death at the age of thirty-six.